A decellularized dermis-containing biological patch for hernia repair and a preparation method thereof

CN122624754BActive Publication Date: 2026-10-27TONGJI HOSPITAL ATTACHED TO TONGJI MEDICAL COLLEGE HUAZHONG SCI TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611143424.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27
Estimated Expiration
2046-07-30

AI Technical Summary

Technical Problem

[0004]针对上述情况,为克服现有技术的缺陷,本发明提供了一种用于疝修补的含脱细胞真皮生物补片及其制备方法,过构建非对称双面结构,在脱细胞真皮基质腹腔侧位置形成含改性鞣酸锌纳米复合物的生物多糖防粘连涂层,腹壁侧保留多孔结构,同时采用京尼平渗透交联与EDC/NHS表面微交联的梯度双重交联技术,并以同源胶原寡肽为模板制备的改性鞣酸锌纳米复合物,实现物理屏障、抗氧化抗炎、接触抑菌、力学与降解速率协同调控、低免疫原性促进组织整合的多重功能,有效解决了目前市场上疝修补用生物补片难以同时兼顾腹腔侧防粘连与腹壁侧组织长入、支撑力等力学强度与体内降解速率不匹配、以及补片中残留的免疫原性物质导致慢性炎症和组织结合效果欠佳的问题

Benefits of technology

[0024]本方案提出了一种用于疝修补的含脱细胞真皮生物补片及其制备方法,通过在脱细胞真皮基质的单侧面形成含改性鞣酸锌纳米复合物的防粘连涂层,在植入疝环缺损部位后遇腹腔渗液等可迅速润湿、不排斥,进一步形成连续水化层,减少摩擦和纤维蛋白沉积,避免与脏器或人体组织粘连;同时,改性鞣酸锌纳米复合物中的鞣酸多酚结构能够清除过量活性氧,抑制氧化应激诱导的炎症反应,促使巨噬细胞向M2型极化,促进胶原沉积、组织修复与再生,减少纤维蛋白渗出和粘连组织的形成,同时锌离子与细菌细胞膜上的负电荷结合产生抑菌作用,降低感染风险,进一步降低粘连的概率,通过物理屏障、抗氧化抗炎和接触抑菌三重机制的协同作用,实现生物补片在腹腔疝病临床中长效可靠的防粘连效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122624754B_ABST
    Figure CN122624754B_ABST
Patent Text Reader

Abstract

The application discloses a kind of for hernia repair containing acellular dermis biological patch and preparation method thereof, belong to biomedical material field, raw material includes acellular porcine dermis layer matrix 90-110 parts, genipin 0.1-0.2 parts, EDC 0.8-2.5 parts, NHS 0.3-1 part, carboxymethyl chitosan 3-8 parts, sodium hyaluronate 1.5-4 parts, chondroitin sulfate 0.5-2 parts, glycerol 2-5 parts, modified zinc tannate nanocomposite 3-12 parts, effectively solve the problems that existing hernia repair patch anti-adhesion and tissue ingrowth is difficult to coordinate, support strength and degradation rate are not matched, foreign body exists in human tissue for a long time and leads to inflammation, by introducing anti-adhesion coating containing zinc tannate coordination nanocomposite and asymmetric double-sided structure, the patch realizes abdominal cavity side long-acting anti-adhesion, abdominal wall side rapid tissue integration and controllable degradation and mechanical support under low immunogenicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically referring to a decellularized dermal biological patch for hernia repair and its preparation method. Background Technology

[0002] Hernia repair surgery is a clinically recognized and commonly used method with the best efficacy and lowest recurrence rate. It can be divided into synthetic polymer material patches and biological patches. Synthetic patches have excellent mechanical properties such as support strength. Biological patches are derived from natural tissues and undergo decellularization to remove immunogenic components while retaining the collagen fiber network scaffold structure. They show advantages in tissue compatibility and regeneration repair. Decellularized dermal matrix, as one of the important sources of biological patches, has been tried in the repair of abdominal wall hernias and inguinal hernias. Its preparation process and physicochemical treatment path have also become the research focus in this field.

[0003] However, while existing synthetic polymer patches for hernia repair exhibit excellent mechanical properties in clinical applications, their long-term presence in the human body can easily lead to adhesions to the abdominal cavity or inflammation due to foreign body reactions. Although bio-based patches possess good biocompatibility, they suffer from a mismatch between degradation rate and tissue regeneration process. Excessive degradation results in insufficient early mechanical support, while excessive degradation hinders the replacement of the patch by new tissue, making it difficult to establish a more effective support. Furthermore, if the patch detaches due to weak interfacial bonding or premature degradation, the residual immunogenic foreign body can also cause inflammation, thus limiting the application effect of bio-based patches. Therefore, there is an urgent need for a bio-based patch that combines controllable degradation, stable anti-adhesion, and low immunogenicity to meet the pressing need for long-lasting and safe implants in current clinical hernia repair procedures. Summary of the Invention

[0004] To address the above issues and overcome the shortcomings of existing technologies, this invention provides a decellularized dermal biological patch for hernia repair and its preparation method. By constructing an asymmetric double-sided structure, a biopolysaccharide anti-adhesion coating containing modified zinc tannate nanocomposite is formed on the abdominal side of the decellularized dermal matrix, while the porous structure is retained on the abdominal wall side. Simultaneously, a gradient dual cross-linking technology combining genipin permeation cross-linking and EDC / NHS surface micro-cross-linking is employed. The modified zinc tannate nanocomposite, prepared using homologous collagen oligopeptides as a template, achieves multiple functions including physical barrier, antioxidant and anti-inflammatory effects, contact antibacterial properties, synergistic regulation of mechanical properties and degradation rates, and low immunogenicity promoting tissue integration. This effectively solves the problems currently faced by commercially available biological patches for hernia repair, such as difficulty in simultaneously achieving anti-adhesion on the abdominal side and tissue ingrowth on the abdominal wall side, mismatch between mechanical strength (support force, etc.) and in vivo degradation rate, and the chronic inflammation and poor tissue integration caused by residual immunogenic substances in the patch.

[0005] The technical solution adopted in this invention is as follows: This invention proposes a decellularized dermal biological patch for hernia repair and its preparation method, comprising the following raw materials in parts by weight: 90-110 parts of decellularized porcine dermal matrix, 0.1-0.2 parts of genipin, 0.8-2.5 parts of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), 0.3-1 parts of N-hydroxysuccinimide (NHS), 3-8 parts of carboxymethyl chitosan, 1.5-4 parts of sodium hyaluronate, 0.5-2 parts of chondroitin sulfate, 2-5 parts of glycerol, and 3-12 parts of modified zinc tannate nanocomposite.

[0006] Furthermore, the modified zinc tannate nanocomposite is prepared using the following method:

[0007] S1. Porcine dermal skin is minced into strips of 5–10 mm, rinsed, and then enzymatically hydrolyzed with trypsin and type I collagenase. The enzymes are then inactivated by heating, the supernatant is collected by centrifugation, and then the supernatant is fractionated by ultrafiltration membrane. The permeate with a molecular weight between 0.3 kDa and 1.0 kDa is collected and freeze-dried to obtain porcine dermal collagen oligopeptides.

[0008] S2. Dissolve the porcine dermal collagen oligopeptides obtained in step S1 in phosphate buffer, adjust the pH to 8-9, add tannic acid solution and stir to fully combine the tannic acid with the collagen oligopeptides to form a precursor dispersion;

[0009] S3. The zinc salt solution is slowly added to the precursor dispersion obtained in step S2 and stirred to carry out a coordination reaction, so that zinc ions and tannic acid can form heterogeneous nuclei and coordinate growth on the surface of collagen oligopeptides, forming nanoparticles with collagen oligopeptides as the core and zinc tannate coordination network as the shell. The free ions are then removed by ultrafiltration purification using an ultrafiltration membrane with a molecular weight cutoff of 100 kDa. The ultrafiltration solution is changed 3-5 times until no free zinc ions and free tannic acid can be detected in the filtrate. The solution is concentrated to a solid content of 10% (w / v) to obtain the modified zinc tannate nanocomposite stock solution.

[0010] Further, in step S1, the mass concentration of the trypsin is 0.15-0.25%, the enzymatic hydrolysis temperature is 35-38℃, and the enzymatic hydrolysis time is 2.5-3.5 hours; the mass concentration of the type I collagenase is 0.08-0.15%, the enzymatic hydrolysis temperature is 35-38℃, and the enzymatic hydrolysis time is 4-6 hours; the temperature for inactivating the enzyme by heating is 85-95℃, and the time is 10-20 minutes; the molecular weight cutoff of the ultrafiltration membrane is 10kDa, 3kDa, and 0.3kDa, respectively.

[0011] Further, in step S2, the initial mass concentration of the porcine dermal collagen oligopeptide in phosphate buffer is 1.6-3.0 mg / mL; the mass ratio of tannic acid to porcine dermal collagen oligopeptide is (0.3-0.6):1; the temperature conditions for the stirring process are 35-38℃, the stirring speed is 180-220 rpm, the stirring time is 25-40 minutes, and the pH is maintained between 7.2 and 7.5 during the stirring process.

[0012] Further, in step S3, the zinc salt is selected from one or more of zinc nitrate, zinc chloride, and zinc sulfate, and the molar ratio of zinc ions to tannic acid is 1:(2-3).

[0013] Furthermore, in step S3, during the coordination reaction, the zinc salt solution is added at a rate of 0.3-0.6 mL / min, and the stirring speed is 280-320 rpm; the coordination reaction temperature is maintained at 35-38℃, the reaction time is 60-90 minutes, and the pH is maintained at 7.0-7.6 during the reaction.

[0014] Furthermore, a method for preparing a decellularized dermal biological patch for hernia repair includes the following steps:

[0015] (1) The decellularized dermal matrix was placed in a genipin solution and cross-linked under vacuum. Then it was transferred to a mixed cross-linking solution of EDC and NHS for surface cross-linking. After rinsing, a gradient double cross-linked decellularized dermal matrix was obtained.

[0016] (2) Dissolve the stock solution of carboxymethyl chitosan, sodium hyaluronate, chondroitin sulfate, glycerol, and modified zinc tannate nanocomposite in deionized water, stir evenly, filter and sterilize to obtain the coating solution.

[0017] (3) The gradient double cross-linked decellularized dermal matrix obtained in step (1) is spread in a mold, and the coating liquid obtained in step (2) is poured evenly on one side of the surface. Then, it is pre-frozen, deep-frozen, and freeze-dried in sequence to make the coating liquid form a film in situ on the side, while the other side remains exposed with a porous and rough morphology to obtain the patch blank. After rinsing to remove residual chemical reagents and sterilizing, the patch blank is used to obtain a decellularized dermal biological patch for hernia repair.

[0018] Further, in step (2), the vacuum degree of the vacuum environment is -0.08 to -0.09 MPa, the temperature of the permeation crosslinking is 35-38℃, and the time is 12-24 hours; in the mixed crosslinking solution of EDC and NHS, the solvent is anhydrous ethanol and phosphate buffer with a volume ratio of 1:4 and a pH of 5.5-6.0; the temperature of the surface crosslinking is 4-8℃, and the time is 2-4 hours; after the crosslinking is completed, it is quenched with 0.1 mol / L glycine solution for 30 minutes.

[0019] Further, in step (1), the stirring process involves first dissolving carboxymethyl chitosan, sodium hyaluronate, chondroitin sulfate, and glycerol in deionized water, and stirring at 30-40°C and 200-300 rpm until completely dissolved to obtain a premixed solution; then adding the modified zinc tannate nanocomposite stock solution to the premixed solution, and continuing to stir for 20-40 minutes to ensure uniform dispersion, maintaining the pH at 6.8-7.4, and finally sterilizing through a 0.22 μm filter membrane to obtain the coating solution.

[0020] Further, in step (3), the pre-freezing temperature is -18 to -25°C and the time is 1.4 to 3.2 hours, the deep freezing temperature is -75 to -90°C and the time is 3 to 5 hours, the freeze drying first raises the temperature from -35°C to 0°C at a rate of 0.1 to 0.3°C / min and maintains it for 24 to 36 hours, and then raises the temperature from 0°C to 20°C at a rate of 0.1 to 0.2°C / min and maintains it for 6 to 15 hours.

[0021] Furthermore, the sterilization method is gamma-ray irradiation sterilization, with a gamma-ray irradiation dose of 25-35 kGy and a Dmax / Dmin ratio of no more than 1.5.

[0022] Optionally, the sterilization method is ethylene oxide sterilization. The patch is placed in a sterilization bag and placed in an ethylene oxide sterilization cabinet. The temperature is set to 35-40℃, the relative humidity is 40-50%, and the ethylene oxide concentration is 400-800 mg / L. Sterilization is carried out for 4-6 hours. After sterilization, ventilation is carried out to remove residual ethylene oxide.

[0023] The beneficial effects achieved by the present invention using the above solution are as follows:

[0024] This solution proposes a decellularized dermal bio-patch for hernia repair and its preparation method. An anti-adhesion coating containing a modified zinc tannate nanocomposite is formed on one side of the decellularized dermal matrix. After implantation at the hernia ring defect site, it can be rapidly wetted by peritoneal exudate without rejection, further forming a continuous hydration layer, reducing friction and fibrin deposition, and preventing adhesion to organs or human tissues. Simultaneously, the tannic acid polyphenol structure in the modified zinc tannate nanocomposite can scavenge excess reactive oxygen species, inhibit oxidative stress-induced inflammatory responses, promote macrophage M2 polarization, promote collagen deposition, tissue repair and regeneration, and reduce fibrin exudation and adhesion formation. Furthermore, zinc ions bind to the negative charge on bacterial cell membranes, producing an antibacterial effect, reducing the risk of infection, and further reducing the probability of adhesion. Through the synergistic effect of physical barrier, antioxidant and anti-inflammatory, and contact antibacterial mechanisms, the bio-patch achieves a long-lasting and reliable anti-adhesion effect in the clinical treatment of abdominal hernia.

[0025] Through the zero-length cross-linking of EDC / NHS, catalysis is carried out on the surface of collagen fibers, promoting the amidation reaction between carboxyl and amino groups and enhancing the surface layer's resistance to enzymatic degradation. Meanwhile, genipin penetrates deep into the collagen fibers of the patch and forms a stable cross-linked structure with collagen, significantly improving the tensile strength and suture tear resistance of the patch. At the same time, zinc ions in the modified zinc tannate nanocomposite inhibit the activity of proteases, preventing excessively rapid degradation of the surface layer. Collagen oligopeptides bind to the decellularized dermal matrix, and tannic acid polyphenols form hydrogen bonds and π-π interactions with collagen amino groups and genipin, strengthening fixation and preventing coating peeling. This results in the patch exhibiting gradually increasing degradation resistance from the surface to the interior after implantation. The easily degradable surface layer of the patch is preferentially degraded, exposing cell binding sites within the patch, while the more degradation-resistant internal region provides support for the gradual replacement process of new tissue. The three factors work synergistically to match the patch degradation process with the hernia repair process, avoiding hernia recurrence or foreign body retention that could lead to inflammation due to excessively rapid or slow patch degradation.

[0026] By decellularizing porcine dermal raw materials and using α-1,3-galactosidase to specifically deactivate rejection antigens, the immune and inflammatory responses triggered after patch implantation are significantly reduced. The porcine dermal collagen oligopeptides in the modified zinc tannate nanocomposite are homologous to the decellularized dermal matrix and rich in integrin α2β1 recognition sequences such as GFOGER, guiding human fibroblasts and smooth muscle cells to migrate and proliferate along the porous surface of the patch, promoting the deposition and remodeling of new collagen fibers, and achieving patch-hernia tissue integration. Simultaneously, natural extracellular matrix components such as chondroitin sulfate and hyaluronic acid maintain suitable hydrophilicity and porous structure, providing channels for nutrient transport and metabolic waste removal, preventing fibrous capsule formation, minimizing immune rejection, and promoting the growth of human tissue into the patch. Attached Figure Description

[0027] Figure 1 The images show the tissue results of various samples of the decellularized dermal biological patch for hernia repair proposed in this invention; wherein, A is the patch structure diagram of Example 1, B is the SEM microscopic surface structure diagram of Example 1, C is the staining diagram of the patch and surrounding tissue of Example 1, D is the patch structure diagram of Comparative Example 1, E is the SEM microscopic surface structure diagram of Comparative Example 1, and F is the staining diagram of the patch and surrounding tissue of Comparative Example 1.

[0028] Figure 2The images show the EDS and mass spectrometry results of a modified zinc tannate nanocomposite containing a decellularized dermal biological patch for hernia repair proposed in this invention. A is the mass spectrum of the modified zinc tannate nanocomposite; B is the EDS spectrum of the modified zinc tannate nanocomposite; C is the SEM microstructure of the modified zinc tannate nanocomposite; D is the surface distribution map of carbon (C) in the modified zinc tannate nanocomposite; E is the surface distribution map of nitrogen (N) in the modified zinc tannate nanocomposite; F is the surface distribution map of oxygen (O) in the modified zinc tannate nanocomposite; and G is the surface distribution map of zinc (Zn) in the modified zinc tannate nanocomposite.

[0029] Figure 3 The image shows the oxidative stress and inflammatory factors of various samples of a decellularized dermal biological patch for hernia repair proposed in this invention on the 14th day after surgery.

[0030] Figure 4 This is a comparative analysis chart of tissue adhesion scores for various samples of a decellularized dermal biological patch for hernia repair proposed in this invention.

[0031] Figure 5 This is a comparison chart of the degradation rate test results of various samples of the decellularized dermal biological patch for hernia repair proposed in this invention;

[0032] Figure 6 This is a comparison chart of the tensile strength test results of various samples of the decellularized dermal biological patch for hernia repair proposed in this invention;

[0033] Figure 7 This is a graph showing the analysis results of collagenase sensitivity and antibacterial experiments of various samples of a decellularized dermal biological patch for hernia repair proposed in this invention.

[0034] Figure 8 This is a comparative diagram of serum immunological test results for various samples of a decellularized dermal biological patch for hernia repair proposed in this invention.

[0035] Figure 9 Comparative images of macrophages and collagen in various samples of a decellularized dermal biological patch for hernia repair proposed in this invention;

[0036] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation

[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention were purchased through commercial channels.

[0039] The decellularized porcine dermal matrix (lyophilized tablets) used in this invention were purchased from Jiangsu Youchuang Biomedical Technology Co., Ltd.; genipin (HPLC ≥ 98%) was purchased from Hefei Bomei Biotechnology Co., Ltd.; 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl, BR, ≥ 99%) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; N-hydroxysuccinimide (NHS, BR, ≥ 99%) was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; carboxymethyl chitosan (degree of deacetylation ≥ 80%, water-soluble) was purchased from Qingdao Boyite Biomaterials Co., Ltd.; sodium hyaluronate (pharmaceutical grade, Mw > 1.0 × 10⁻⁶) was also used. 6 Da) was purchased from Bloomage Biotechnology Co., Ltd.; chondroitin sulfate (reagent grade, purity ≥90%) was purchased from Shanghai Kanglang Biotechnology Co., Ltd.; glycerol (analytical grade AR, content ≥99.0%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0040] Example 1:

[0041] A decellularized dermal biological patch for hernia repair and its preparation method

[0042] This embodiment prepares a decellularized dermal biopatch for hernia repair. Before preparation, a modified zinc tannate nanocomposite of the key functional component is first prepared. In preparing this composite, porcine dermal tissue is minced into strips of 5–10 mm, rinsed, and then enzymatically hydrolyzed with 0.15% trypsin at 35°C for 3.5 hours and 0.08% type I collagenase at 35°C for 6 hours. Then, the enzymes are inactivated by heating to 85°C for 20 minutes. The supernatant is collected by centrifugation and then fractionated by ultrafiltration membranes with molecular weight cutoffs of 10 kDa, 3 kDa, and 0.3 kDa. The permeate with molecular weights between 0.3 kDa and 1.0 kDa is collected and freeze-dried to obtain porcine dermal collagen oligopeptides.

[0043] Next, the obtained porcine dermal collagen oligopeptides were dissolved in phosphate buffer to achieve an initial mass concentration of 1.6 mg / mL. After adjusting the pH to 8, tannic acid solution was added and stirred. The mass ratio of tannic acid to porcine dermal collagen oligopeptides was 0.3:1. The stirring process was carried out at a temperature of 35°C and a stirring speed of 180 rpm for 40 minutes, during which the pH was maintained at 7.2 to ensure that the tannic acid and collagen oligopeptides were fully combined to form a precursor dispersion.

[0044] Subsequently, a zinc salt solution selected from zinc nitrate was added to the obtained precursor dispersion at a dropping rate of 0.3 mL / min. The coordination reaction was carried out for 90 minutes under stirring conditions of 35℃ and 280 rpm. The molar ratio of zinc ions to tannic acid was 1:2. During the reaction, the pH was maintained at 7.0, allowing zinc ions and tannic acid to heterogeneously nucleate and coordinate on the surface of collagen oligopeptides, forming nanoparticles with collagen oligopeptides as the core and zinc tannate coordination network as the shell. The nanoparticles were then purified by ultrafiltration through an ultrafiltration membrane with a molecular weight cutoff of 100 kDa. The ultrafiltration solution was changed 3 times until no free zinc ions and free tannic acid were detected in the filtrate. The solution was concentrated to a solid content of 10% (w / v) to obtain the modified zinc tannate nanocomposite stock solution for later use.

[0045] Next, the modified zinc tannate nanocomposite stock solution prepared above, along with other raw materials, was used to prepare a decellularized dermal biological patch.

[0046] In the specific preparation process, 90 parts of decellularized porcine dermal matrix were first placed in a genipin solution, with 0.1 parts of genipin. Under a vacuum of -0.08 MPa, the matrix was permeated and crosslinked at 35°C for 24 hours. Then, it was transferred to a mixed crosslinking solution composed of EDC and NHS for surface crosslinking, with 0.8 parts of EDC and 0.3 parts of NHS. The solvent of the mixed crosslinking solution was anhydrous ethanol and phosphate buffer with a volume ratio of 1:4 and a pH of 5.5. The surface crosslinking temperature was 4°C and the time was 4 hours. After the crosslinking was completed, the matrix was quenched with 0.1 mol / L glycine solution for 30 minutes. After rinsing, a graded double crosslinked decellularized dermal matrix was obtained.

[0047] Dissolve 3 parts carboxymethyl chitosan, 1.5 parts sodium hyaluronate, 0.5 parts chondroitin sulfate and 2 parts glycerol in deionized water and stir at 30°C and 200 rpm until completely dissolved to obtain a premix. Then add 3 parts of modified zinc tannate nanocomposite stock solution to the premix and continue stirring for 40 minutes to ensure uniform dispersion. Maintain the pH at 6.8 and finally sterilize through a 0.22 μm filter membrane to obtain the coating solution.

[0048] Then, the obtained gradient double cross-linked decellularized dermal matrix was spread in a mold, and the obtained coating liquid was poured evenly on one side of it. It was then subjected to pre-freezing at -18℃ for 3.2 hours, deep freezing at -75℃ for 5 hours, and freeze-drying. The freeze-drying process first raised the temperature from -35℃ to 0℃ at a rate of 0.1℃ / min and maintained it for 36 hours, and then raised the temperature from 0℃ to 20℃ at a rate of 0.1℃ / min and maintained it for 15 hours, so that the coating liquid formed a film in situ on this side, while the other side remained exposed with a porous and rough morphology, thus obtaining the patch blank.

[0049] Finally, the patch blank is rinsed to remove residual chemical reagents and sterilized by 25kGy gamma irradiation to obtain a decellularized dermal biological patch for hernia repair.

[0050] Example 2:

[0051] A decellularized dermal biological patch for hernia repair and its preparation method

[0052] This embodiment prepares a decellularized dermal biopatch for hernia repair. Before preparation, a modified zinc tannate nanocomposite with key functional components is first prepared. In preparing this composite, porcine dermal tissue is minced into strips of 5–10 mm, rinsed, and then enzymatically hydrolyzed with 0.20% trypsin at 36.5°C for 3.0 hours and 0.115% type I collagenase at 36.5°C for 5 hours. The enzymes are then inactivated by heating to 90°C for 15 minutes. The supernatant is collected by centrifugation and then fractionated by ultrafiltration membranes with molecular weight cutoffs of 10 kDa, 3 kDa, and 0.3 kDa. The permeate with molecular weights between 0.3 kDa and 1.0 kDa is collected and freeze-dried to obtain porcine dermal collagen oligopeptides.

[0053] Next, the obtained porcine dermal collagen oligopeptides were dissolved in phosphate buffer to achieve an initial mass concentration of 2.3 mg / mL. After adjusting the pH to 8.5, tannic acid solution was added and stirred. The mass ratio of tannic acid to porcine dermal collagen oligopeptides was 0.45:1. The stirring process was carried out at a temperature of 36.5℃ and a stirring speed of 200 rpm for 32.5 minutes, while maintaining the pH at 7.35 to ensure that the tannic acid and collagen oligopeptides were fully combined to form a precursor dispersion.

[0054] Subsequently, a zinc salt solution selected from zinc chloride was added to the obtained precursor dispersion at a dropping rate of 0.45 mL / min. The coordination reaction was carried out for 75 minutes under stirring conditions of 36.5℃ and 300 rpm. The molar ratio of zinc ions to tannic acid was 1:2.5. During the reaction, the pH was maintained at 7.3, allowing zinc ions and tannic acid to heterogeneously nucleate and coordinate on the surface of collagen oligopeptides, forming nanoparticles with collagen oligopeptides as the core and zinc tannate coordination network as the shell. The nanoparticles were then purified by ultrafiltration through an ultrafiltration membrane with a molecular weight cutoff of 100 kDa. The ultrafiltration solution was changed 4 times until no free zinc ions and free tannic acid were detected in the filtrate. The solution was concentrated to a solid content of 10% (w / v) to obtain the modified zinc tannate nanocomposite stock solution for later use.

[0055] Next, the modified zinc tannate nanocomposite stock solution prepared above, along with other raw materials, was used to prepare a decellularized dermal biological patch.

[0056] In the specific preparation process, 100 parts of decellularized porcine dermal matrix were first placed in a genipin solution, with 0.15 parts of genipin. Under a vacuum of -0.085 MPa, the matrix was permeated and crosslinked at 36.5℃ for 18 hours. Then, it was transferred to a mixed crosslinking solution composed of EDC and NHS for surface crosslinking, with 1.65 parts of EDC and 0.65 parts of NHS. The solvent of the mixed crosslinking solution was anhydrous ethanol and phosphate buffer with a volume ratio of 1:4 and a pH of 5.75. The surface crosslinking temperature was 6℃ and the time was 3 hours. After the crosslinking was completed, the matrix was quenched with 0.1 mol / L glycine solution for 30 minutes. After rinsing, a graded double crosslinked decellularized dermal matrix was obtained.

[0057] 5.5 parts carboxymethyl chitosan, 2.75 parts sodium hyaluronate, 1.25 parts chondroitin sulfate and 3.5 parts glycerol were dissolved in deionized water and stirred at 35°C and 250 rpm until completely dissolved to obtain a premix. Then, 7.5 parts of modified zinc tannate nanocomposite stock solution were added to the premix and stirred for another 30 minutes to ensure uniform dispersion. The pH was maintained at 7.1. Finally, the solution was sterilized through a 0.22 μm filter membrane to obtain the coating solution.

[0058] Then, the obtained gradient double cross-linked decellularized dermal matrix was spread in a mold, and the obtained coating liquid was uniformly poured on one side of it. It was then subjected to pre-freezing at -21.5℃ for 2.3 hours, deep freezing at -82.5℃ for 4 hours, and freeze-drying. The freeze-drying process first raised the temperature from -35℃ to 0℃ at a rate of 0.2℃ / min and maintained it for 30 hours, and then raised the temperature from 0℃ to 20℃ at a rate of 0.15℃ / min and maintained it for 10.5 hours, so that the coating liquid formed a film in situ on this side, while the other side remained exposed with a porous and rough morphology, thus obtaining the patch blank.

[0059] Finally, after rinsing to remove residual chemical reagents, the patch blank is placed in a sterilization bag and then placed in an ethylene oxide sterilizer. The temperature is set at 37°C, the relative humidity at 40%, and the ethylene oxide concentration at 500 mg / L. Sterilization is carried out for 6 hours, followed by ventilation to remove residual ethylene oxide. This yields a decellularized dermal biological patch for hernia repair.

[0060] Example 3:

[0061] A decellularized dermal biological patch for hernia repair and its preparation method

[0062] This embodiment prepares a decellularized dermal biopatch for hernia repair. Before preparation, a modified zinc tannate nanocomposite of the key functional component is first prepared. In preparing this composite, porcine dermal tissue is minced into strips of 5–10 mm, rinsed, and then enzymatically hydrolyzed with 0.25% trypsin at 38°C for 2.5 hours and 0.15% type I collagenase at 38°C for 4 hours. Then, the enzyme is inactivated by heating to 95°C for 10 minutes. The supernatant is collected by centrifugation and then fractionated by ultrafiltration membranes with molecular weight cutoffs of 10 kDa, 3 kDa, and 0.3 kDa. The permeate with molecular weights between 0.3 kDa and 1.0 kDa is collected and freeze-dried to obtain porcine dermal collagen oligopeptides.

[0063] Next, the obtained porcine dermal collagen oligopeptides were dissolved in phosphate buffer to achieve an initial mass concentration of 3.0 mg / mL. After adjusting the pH to 9, tannic acid solution was added and stirred. The mass ratio of tannic acid to porcine dermal collagen oligopeptides was 0.6:1. The stirring process was carried out at a temperature of 38°C and a stirring speed of 220 rpm for 25 minutes, during which the pH was maintained at 7.5 to ensure that the tannic acid and collagen oligopeptides were fully combined to form a precursor dispersion.

[0064] Subsequently, a zinc salt solution selected from zinc sulfate was added to the obtained precursor dispersion at a dropping rate of 0.6 mL / min. The coordination reaction was carried out for 60 minutes under stirring conditions of 38℃ and 320 rpm. The molar ratio of zinc ions to tannic acid was 1:3. During the reaction, the pH was maintained at 7.6, allowing zinc ions and tannic acid to heterogeneously nucleate and coordinate on the surface of collagen oligopeptides, forming nanoparticles with collagen oligopeptides as the core and zinc tannate coordination network as the shell. The nanoparticles were then purified by ultrafiltration through an ultrafiltration membrane with a molecular weight cutoff of 100 kDa. The ultrafiltration solution was changed 5 times until no free zinc ions and free tannic acid were detected in the filtrate. The solution was concentrated to a solid content of 10% (w / v) to obtain the modified zinc tannate nanocomposite stock solution for later use.

[0065] Next, the modified zinc tannate nanocomposite stock solution prepared above, along with other raw materials, was used to prepare a decellularized dermal biological patch.

[0066] In the specific preparation process, 110 parts of decellularized porcine dermal matrix were first placed in a genipin solution, with 0.2 parts of genipin used. Under a vacuum environment of -0.09 MPa, the matrix was permeated and crosslinked at 38°C for 12 hours. Then, it was transferred to a mixed crosslinking solution composed of EDC and NHS for surface crosslinking, with 2.5 parts of EDC and 1 part of NHS used. The solvent of the mixed crosslinking solution was anhydrous ethanol and phosphate buffer with a volume ratio of 1:4 and a pH of 6.0. The surface crosslinking temperature was 8°C and the time was 2 hours. After the crosslinking was completed, the matrix was quenched with 0.1 mol / L glycine solution for 30 minutes. After rinsing, a graded double crosslinked decellularized dermal matrix was obtained.

[0067] Eight parts of carboxymethyl chitosan, four parts of sodium hyaluronate, two parts of chondroitin sulfate, and five parts of glycerol were dissolved in deionized water and stirred at 40°C and 300 rpm until completely dissolved to obtain a premix. Then, 12 parts of the modified zinc tannate nanocomposite stock solution were added to the premix and stirred for another 20 minutes to ensure uniform dispersion. The pH was maintained at 7.4. Finally, the solution was sterilized by passing it through a 0.22 μm filter membrane to obtain the coating solution.

[0068] Then, the obtained gradient double cross-linked decellularized dermal matrix was spread in a mold, and the obtained coating liquid was uniformly poured on one side of it. It was then subjected to pre-freezing at -25℃ for 1.4 hours, deep freezing at -90℃ for 3 hours, and freeze-drying. The freeze-drying process first raised the temperature from -35℃ to 0℃ at a rate of 0.3℃ / min and maintained it for 24 hours, and then raised the temperature from 0℃ to 20℃ at a rate of 0.2℃ / min and maintained it for 6 hours, so that the coating liquid formed a film in situ on this side, while the other side remained exposed with a porous and rough morphology, thus obtaining the patch blank.

[0069] Finally, the patch blank is rinsed to remove residual chemical reagents and sterilized by 35kGy gamma irradiation to obtain a decellularized dermal biological patch for hernia repair.

[0070] Comparative Example 1:

[0071] The specific implementation method is the same as in Example 1, except that no modified zinc tannate nanocomposite stock solution is added when preparing the coating liquid, and the other operation steps are exactly the same.

[0072] This comparative study, by removing the modified zinc tannate nanocomposite, compared and observed whether there were significant differences in the effects of patch implantation on inhibiting oxidative stress, reducing inflammatory response, preventing bacterial infection, and reducing the incidence of adhesion, thereby verifying whether the modified zinc tannate nanocomposite is necessary in this approach.

[0073] Comparative Example 2:

[0074] The specific implementation method is the same as in Example 1, except that the modified zinc tannate nanocomposite is replaced with an equal mass of silver nanoparticle solution (particle size of about 20 nm, mass concentration of 0.5 mg / mL), and the other operation steps are exactly the same.

[0075] This comparative example compares commonly available antibacterial nanomaterials with the modified zinc tannate nanocomposite in this solution to determine whether they possess the same effects in terms of antibacterial and antioxidant properties, long-lasting anti-adhesion, and tissue repair, thereby verifying whether the modified zinc tannate nanocomposite is irreplaceable.

[0076] Comparative Example 3:

[0077] The specific implementation method is the same as in Example 1, except that the coating liquid is replaced with modified zinc tannate nanocomposite, that is, carboxymethyl chitosan, sodium hyaluronate and chondroitin sulfate are not added. The modified zinc tannate nanocomposite is mixed with glycerin and then directly and uniformly sprayed onto one side of the surface of the gradient double cross-linked decellularized dermal matrix. The amount of spraying is equivalent to the total amount of modified zinc tannate nanocomposite contained in the coating liquid in Example 1. The other operation steps are exactly the same.

[0078] This comparative example compares the modified zinc tannate nanocomposite with the example to observe whether there are differences in performance such as anti-adhesion effect, cell migration, and tissue integration, and to verify whether there is a synergistic effect between the modified zinc tannate nanocomposite and other natural extracellular matrix components (carboxymethyl chitosan, sodium hyaluronate, and chondroitin sulfate) in the coating solution.

[0079] Experimental Example 1:

[0080] Experimental grouping: 72 healthy adult male SD rats, weighing approximately 250g, were randomly divided into 6 groups of 12 rats each. Biological patches were prepared according to the processes of Examples 1-3 and Comparative Examples 1-3, and used as experimental and control samples for the 6 groups of animals. The experimental groups were Examples 1, 2, and 3, and the control groups were Comparative Examples 1, 2, and 3.

[0081] Establishment of rat abdominal wall hernia defects combined with intestinal adhesions: After anesthetizing the rats, a longitudinal incision of about 3 cm was made in the midline of the rat's abdomen to expose the anterior sheath of the rectus abdominis muscle; a piece of full-thickness abdominal wall muscle and peritoneum with a diameter of 1.5 cm was removed to create an abdominal wall defect; each group of patches was trimmed into circles with a diameter of 2.0 cm and implanted into the defect, with the coated side facing the abdominal cavity and the exposed side facing the abdominal wall muscle, and finally the skin incision was sutured.

[0082] Postoperative adhesion scoring: Four rats were sacrificed on postoperative days 7, 14 and 28. The abdominal cavity was opened to observe the adhesion between the patch and the abdominal organs (intestines, greater omentum). The scores were set from 0 to 4, where 0 points meant no adhesion, 1 point meant slight membranous adhesion that could be bluntly separated, 2 points meant moderate adhesion that required sharp separation, 3 points meant severe and extensive adhesion, and 4 points meant dense adhesion with tissue embedding.

[0083] Histological analysis: The patch and surrounding tissue were taken for HE staining and Masson staining to observe the degree of inflammatory cell infiltration, fibrin deposition, and number of new blood vessels.

[0084] Oxidative stress and inflammatory factor detection: Tissue homogenate around the patch was taken, and the activity of superoxide dismutase (SOD) and the content of malondialdehyde (MDA) were measured to assess antioxidant capacity; the levels of related factors such as TNF-α, IL-6, and IL-10 in the tissue homogenate were detected by ELISA to assess anti-inflammatory and repair-promoting capabilities.

[0085] Experimental results are as follows Figure 1 , Figure 2 , Figure 3 , Figure 4 As shown, in the adhesion scores at each postoperative time point, the Example group was significantly lower than all the Comparative groups, and the scores remained stable or even slightly decreased over time. The adhesion scores of Comparative Examples 1 and 3 continued to rise, indicating that the Example group possessed a durable and stable anti-adhesion ability. Oxidative stress indicators showed that the Example group had higher antioxidant enzyme activity and lower lipid peroxidation products, demonstrating excellent antioxidant microenvironment regulation effects. Regarding the inflammatory factor spectrum, the Example group showed lower levels of pro-inflammatory factors including interleukin-1β, interferon-γ, interleukin-17A, tumor necrosis factor-α, and interleukin-6, while anti-inflammatory factors interleukin-4, interleukin-13, and interleukin-10 were significantly increased, showing a clear tendency towards M2 macrophage polarization. Simultaneously, transforming growth factor β1 was maintained at an appropriate level, avoiding excessive... Fibrosis was observed. Chemokines such as monocyte chemoattractant protein 1, macrophage inflammatory protein 1α, and RANTES showed low expression in the Example group, suggesting that the recruitment of local inflammatory cells was effectively inhibited. Among matrix remodeling-related factors, matrix metalloproteinases 2 and 9 showed high activity while matrix metalloproteinase inhibitor 1 was relatively moderate in the Example group, indicating a dynamic balance between matrix degradation and remodeling, which is conducive to orderly tissue integration. The ratio of matrix metalloproteinase inhibitor 1 to matrix metalloproteinase 9 was significantly increased in the Comparative Group, reflecting a tendency towards fibrosis. Vascular endothelial growth factor was moderately expressed in the Example group, avoiding abnormal angiogenesis. In summary, the decellularized dermal biological patch containing modified zinc tannate nanocomposite can achieve a long-term and reliable anti-adhesion effect in a rat abdominal wall hernia model through the synergistic effect of physical barrier, antioxidant and anti-inflammatory, and contact antibacterial mechanisms.

[0086] Experimental Example 2:

[0087] Experimental grouping: 36 healthy adult male New Zealand white rabbits, weighing approximately 2.5 kg, were randomly divided into 6 groups of 6 rabbits each. Biological patches were prepared according to the processes of Examples 1-3 and Comparative Examples 1-3 and were used in the 6 groups of animals as experimental and control groups, respectively. The experimental groups were Examples 1, 2, and 3, and the control groups were Comparative Examples 1, 2, and 3.

[0088] Establishment of rabbit abdominal wall hernia defect samples: After anesthetizing the rabbits, a 5cm incision was made in the midline of the rabbit abdomen to expose the anterior sheath of the rectus abdominis muscle; a 2.0cm diameter full-thickness abdominal wall tissue was removed to create a defect; each group of patches was trimmed into a 2.5cm diameter circle and implanted into the defect (with the coating facing the abdominal cavity), and the incision was sutured to fix it.

[0089] Patch degradation rate determination: At weeks 3, 6, 9, and 12 post-surgery, patches and surrounding tissues were collected from three rabbits each. After removing attached tissue, the patches were weighed, and the percentage of remaining weight was calculated (remaining weight / initial weight × 100%). Adjacent normal abdominal wall tissue was also taken as a control.

[0090] Mechanical strength test: Patch samples were taken at 4, 8 and 12 weeks after surgery. The tensile strength and suture tear force were measured using a universal testing machine and compared with the preoperative patch.

[0091] Tissue section analysis: HE staining and Sirius red staining were used to observe the degradation interface of the patch, the amount of newly deposited collagen, the distribution of inflammatory cells, and to measure the remaining thickness of the patch and the depth of the degradation front.

[0092] Collagenase sensitivity test: Take the patch sample 4 weeks after surgery, cut it into 1cm×1cm pieces, place it in PBS containing type I collagenase (0.1mg / mL), incubate at 37℃ for 24 hours, weigh the dry weight before and after degradation, and calculate the enzymatic weight loss rate.

[0093] Antibacterial test: In the third week after surgery, a swab was taken from the surface of the patch under aseptic conditions, inoculated onto LB agar plates, and incubated at 37°C for 24 hours. Colony forming units (CFU) were counted.

[0094] Table 1. Changes in suture tear force over time (unit: N)

[0095]

[0096] Experimental results are as follows Figure 5 , Figure 6 , Figure 7As shown in Table 1, the degradation rate of patches in Examples 1-3 after implantation showed a trend of slow initial degradation followed by rapid degradation. The remaining weight percentage, tensile strength retention rate, and suture tear force were significantly higher than those in the control group, while the enzymatic loss rate was significantly lower. Tissue sections showed a clear degradation interface, abundant and regularly arranged new collagen deposition, mild inflammatory response, and predominantly repair-type macrophages. Comparative Example 1, lacking the modified zinc tannate nanocomposite, degraded too quickly, resulting in a sharp decrease in mechanical strength and suture tear force. Tissue sections showed patch structure fragmentation, less new collagen, and extensive infiltration of inflammatory cells. Although the degradation rate of Comparative Example 2 was similar to that of the Example groups, its mechanical properties deteriorated faster, and the suture tear force decreased significantly. Tissue sections showed foreign body giant cells and a large number of lymphocytes. The original sample exhibited poor tissue integration. Comparative Example 3, lacking natural extracellular matrix components in its coating, showed uneven degradation, with localized rapid degradation followed by a slowdown. Its mechanical properties and suture tear strength were unsatisfactory. Tissue sections revealed irregular degradation interfaces, uneven deposition of new collagen, and a tendency for fibrous capsule formation. Furthermore, antibacterial experiments showed that the bacterial load on the patch surface of the Example group was lower than that of Comparative Examples 1 and 3, approaching the level of Comparative Example 2, demonstrating that the Example group possessed effective contact antibacterial capabilities. In summary, the Example prepared using this scheme exhibits a controllable degradation process and stable mechanical support, effectively inhibiting excessively rapid degradation, promoting orderly tissue regeneration and integration, while simultaneously reducing inflammatory responses, achieving a good match between patch degradation and hernia tissue repair processes.

[0097] Experimental Example 3:

[0098] Experimental grouping: Six healthy miniature pigs, weighing approximately 15 kg, were randomly divided into three groups of two. Biological patches were prepared according to the processes of Examples 1-3 and Comparative Examples 1-3 and were used in the experimental and control groups, respectively. The experimental groups were Examples 1, 2, and 3, and the control groups were Comparative Examples 1, 2, and 3.

[0099] Establishing a laparoscopic hernia repair sample in pigs: After general anesthesia, an 8cm longitudinal incision was made along the midline of the pig's abdomen to expose the anterior sheaths of the bilateral rectus abdominis muscles; 2cm diameter full-thickness abdominal wall tissue was removed from both sides to create symmetrical defects, with a distance of at least 5cm between the two defects to avoid interference; a corresponding patch was implanted in each pig, such as patch 1 of Example 1 on the left side and patch 1 of Comparative Example 1 on the right side, with 2 pigs per group; the incision was closed after suturing and fixation.

[0100] Serological immunological tests: Blood samples were collected before surgery and at 1, 2, 4 and 8 weeks after surgery to detect the titers of IgG and IgM antibodies in serum, as well as the levels of complement C3a and C5a, to assess the systemic immune response.

[0101] Local inflammation score: Pig patch and surrounding tissue were taken at 4 and 8 weeks postoperatively, stained with hematoxylin and eosin (HE), and the density of inflammatory cell infiltration (0-4 grade) was assessed by a pathologist in a blind manner.

[0102] Macrophage polarization analysis: Immunohistochemical staining was used to detect CD68 (total macrophages), CD86 (M1 type pro-inflammatory marker) and CD163 (M2 type anti-inflammatory repair marker), and the M2 / M1 ratio was calculated.

[0103] Cell migration and proliferation: At week 4 post-surgery, patch tissue was taken, and immunofluorescence staining was used to detect vimentin (fibroblasts) and α-SMA (smooth muscle cells), and the density of positive cells was counted.

[0104] New collagen deposition: Sirius red staining with polarized light observation, quantitative analysis of the area ratio of type I and type III collagen.

[0105] Mechanical integration test: At the 8th week after surgery, a dumbbell-shaped specimen was made from the junction of the patch and the tissue to test the tensile breaking strength and assess the bonding strength between the patch and the tissue.

[0106] Table 2 Results of each test item

[0107]

[0108] Experimental results are as follows Figure 8 , Figure 9 As shown in Table 2, Examples 1-3 exhibited significant advantages in all detection indicators. Their serum immunoglobulin and complement levels were significantly lower than those of all control groups, and the local inflammatory response was also milder. At the same time, macrophage polarization showed a clear repair-oriented dominant characteristic, and the M2 / M1 ratio was higher than that of the control group. In terms of cell migration and proliferation, the density of fibroblasts and smooth muscle cells in the examples was significantly higher than that in the control group. The newly formed collagen was deposited in an orderly manner, and the ratio of type I to type III collagen was closer to that of normal fascia tissue. The integration of the patch with the tissue was also the highest in the examples. In contrast, Comparative Example 1, due to the lack of modified zinc tannate nanocomposite, Comparative Example 2, due to the potential cytotoxicity of nano-silver, and Comparative Example 3, due to the incomplete coating components, all showed higher immunogenicity, weaker anti-inflammatory ability, and lower tissue integration ability to varying degrees, and the degree of cell growth was limited. These results indicate that the decellularized dermal biological patch of the present invention can effectively reduce immune rejection, significantly promote the migration and proliferation of host cells into the patch, and guide the orderly remodeling of newly formed collagen, thereby achieving rapid and firm integration of the patch with the hernia tissue.

[0109] Experiment Example 4:

[0110] Experimental samples: Prepare samples from Examples 1, 2, and 3, with 6 replicates in each group.

[0111] Sample preparation: Take 3 patches from each of the above three groups (n=3), and cut out a 1cm×1cm size from the central area of ​​the coated side.

[0112] Total polyphenol content determination: Take the sample and add 3 mL of Folin-Ciocalteu reagent (diluted 10 times), shake well and let stand for 5 minutes; add 2 mL of sodium carbonate (7.5%) solution, mix well and keep warm in a 50℃ water bath for 30 minutes; cool to room temperature and measure the absorbance at 760 nm. Calculate the total polyphenol content (mg / mL) according to the gallic acid standard curve; use the unsterilized patch as the baseline value to calculate the polyphenol retention rate.

[0113] Determination of zinc ion content: Take 2.0 mL of the above extract, add 10 M ammonium chloride buffer solution, and then add a small amount of Eriochrome Black T indicator; titrate with 0.01 M EDTA until the solution changes from wine red to pure blue, and record the volume of EDTA consumed; calculate the zinc ion content and compare it with the unsterilized patch to obtain the zinc ion retention rate.

[0114] DPPH free radical scavenging rate determination: Immerse each group of samples in 1 mL of DPPH ethanol solution (0.1 mM), shake at 37℃ in the dark for 30 minutes; take the supernatant, measure the absorbance at 517 nm, and record the free radical scavenging rate (%).

[0115] Cytotoxicity assay: Each patch disc (8 mm in diameter) was placed in a 96-well plate containing L929 mouse fibroblasts and cultured at 37°C for 48 hours. MTT solution was then added, and the absorbance at 570 nm was measured to calculate the cell death rate.

[0116] Inhibition zone test: Staphylococcus aureus (ATCC 25923) suspension (1×106 CFU / mL) was spread on MH agar plates; patch samples (6 mm diameter discs) of each group were attached to the surface of the plates and incubated at 37℃ for 24 hours; the diameter of the inhibition zone (mm) was measured and the average value of each group was taken.

[0117] Table 3 Test results data for each item

[0118]

[0119] The experimental results are shown in Table 3. Example 2, sterilized with ethylene oxide, is superior to Examples 1 and 3, which were irradiated with gamma rays, in terms of total polyphenol retention, antioxidant activity, and antibacterial effect. There is no significant difference in zinc ion retention. This experiment shows that ethylene oxide sterilization can better protect the structure and activity of the modifier, and its residual trace toxicity is far below the safety limit. Gamma ray irradiation sterilization will cause partial damage to the polyphenol structure in the modified zinc tannate nanocomposite, but the overall damage is controllable, the performance can meet the application requirements, and it is less toxic and safer to use.

[0120] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0121] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0122] The present invention and its embodiments have been described above. This description is not restrictive. The accompanying drawings are only one embodiment of the present invention. The actual structure is not limited to this. In short, if a person skilled in the art is inspired by this description and designs a similar structure and embodiment without departing from the spirit of the present invention, such design should fall within the protection scope of the present invention.

Claims

1. A decellularized dermal biological patch for hernia repair, characterized in that: The raw materials include the following parts by weight: 90-110 parts of decellularized porcine dermal matrix, 0.1-0.2 parts of genipin, 0.8-2.5 parts of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide EDC, 0.3-1 parts of N-hydroxysuccinimide NHS, 3-8 parts of carboxymethyl chitosan, 1.5-4 parts of sodium hyaluronate, 0.5-2 parts of chondroitin sulfate, 2-5 parts of glycerol, and 3-12 parts of modified zinc tannate nanocomposite. The modified zinc tannate nanocomposite was prepared using the following method: S1. After mincing and rinsing, porcine dermal skin is enzymatically hydrolyzed with trypsin and type I collagenase in sequence. Then, the enzymes are inactivated by heating, the supernatant is collected by centrifugation, and the supernatant is then fractionated by ultrafiltration membrane. The permeate is collected and freeze-dried to obtain porcine dermal collagen oligopeptides. S2. Dissolve the porcine dermal collagen oligopeptide obtained in step S1 in phosphate buffer, adjust the pH to 8-9, add tannic acid solution and stir to form a precursor dispersion; S3. Add the zinc salt solution to the precursor dispersion obtained in step S2 at a slow dropping rate and stir to carry out a coordination reaction to form nanoparticles. Then, remove free ions by ultrafiltration purification using an ultrafiltration membrane with a molecular weight cutoff of 100 kDa. Change the ultrafiltration solution 3-5 times until no free zinc ions and free tannic acid can be detected in the filtrate. Concentrate to a solid content of 10% w / v to obtain the modified zinc tannate nanocomposite stock solution. The method for preparing a decellularized dermal biological patch for hernia repair includes the following steps: (1) The decellularized dermal matrix was placed in a genipin solution and cross-linked under vacuum. Then it was transferred to a mixed cross-linking solution of EDC and NHS for surface cross-linking. After rinsing, a gradient double cross-linked decellularized dermal matrix was obtained. (2) Dissolve the stock solution of carboxymethyl chitosan, sodium hyaluronate, chondroitin sulfate, glycerol, and modified zinc tannate nanocomposite in deionized water, stir evenly, filter and sterilize to obtain the coating solution. (3) The gradient double cross-linked decellularized dermal matrix obtained in step (1) is spread in a mold, and the coating liquid obtained in step (2) is poured evenly on one side of the surface. Then, it is pre-frozen, deep-frozen, and freeze-dried in sequence to make the coating liquid form a film in situ on the side, while the other side remains exposed with a porous and rough morphology to obtain the patch blank. After rinsing and sterilizing the patch blank, the decellularized dermal biological patch for hernia repair is obtained.

2. The decellularized dermal biological patch for hernia repair according to claim 1, characterized in that: In step S1, the mass concentration of the trypsin is 0.15-0.25%, the enzymatic hydrolysis temperature is 35-38℃, and the enzymatic hydrolysis time is 2.5-3.5 hours; the mass concentration of the type I collagenase is 0.08-0.15%, the enzymatic hydrolysis temperature is 35-38℃, and the enzymatic hydrolysis time is 4-6 hours; the temperature for inactivating the enzyme by heating is 85-95℃, and the time is 10-20 minutes.

3. The decellularized dermal biological patch for hernia repair according to claim 1, characterized in that: In step S2, the initial mass concentration of the porcine dermal collagen oligopeptide in phosphate buffer is 1.6-3.0 mg / mL; the mass ratio of tannic acid to porcine dermal collagen oligopeptide is (0.3-0.6):1; the temperature conditions for the stirring process are 35-38℃, the stirring speed is 180-220 rpm, the stirring time is 25-40 minutes, and the pH is maintained between 7.2 and 7.5 during the stirring process.

4. The decellularized dermal biological patch for hernia repair according to claim 1, characterized in that: In step S3, the zinc salt is selected from one or more of zinc nitrate, zinc chloride, and zinc sulfate, and the molar ratio of zinc ions to tannic acid is 1:(2-3).

5. A decellularized dermal biological patch for hernia repair according to claim 1, characterized in that: In step S3, during the coordination reaction, the zinc salt solution is added at a rate of 0.3-0.6 mL / min, and the stirring speed is 280-320 rpm; the coordination reaction temperature is maintained at 35-38℃, the reaction time is 60-90 minutes, and the pH is maintained at 7.0-7.6 during the reaction.

6. A method for preparing a decellularized dermal biological patch for hernia repair, wherein the method is used to prepare the decellularized dermal biological patch for hernia repair as described in any one of claims 1-5, characterized in that: Includes the following steps: (1) The decellularized dermal matrix was placed in a genipin solution and cross-linked under vacuum. Then it was transferred to a mixed cross-linking solution of EDC and NHS for surface cross-linking. After rinsing, a gradient double cross-linked decellularized dermal matrix was obtained. (2) Dissolve the stock solution of carboxymethyl chitosan, sodium hyaluronate, chondroitin sulfate, glycerol, and modified zinc tannate nanocomposite in deionized water, stir evenly, filter and sterilize to obtain the coating solution. (3) The gradient double cross-linked decellularized dermal matrix obtained in step (1) is spread in a mold, and the coating liquid obtained in step (2) is poured evenly on one side of the surface. Then, it is pre-frozen, deep-frozen, and freeze-dried in sequence to make the coating liquid form a film in situ on the side, while the other side remains exposed with a porous and rough morphology to obtain the patch blank. After rinsing and sterilizing the patch blank, the decellularized dermal biological patch for hernia repair is obtained.

7. A method for preparing a decellularized dermal biological patch for hernia repair according to claim 6, characterized in that: In step (1), the vacuum level of the vacuum environment is -0.08 to -0.09 MPa, the temperature of the permeation crosslinking is 35-38℃, and the time is 12-24 hours; in the mixed crosslinking solution of EDC and NHS, the solvent is anhydrous ethanol and phosphate buffer with a volume ratio of 1:4 and a pH of 5.5-6.0; the temperature of the surface crosslinking is 4-8℃, and the time is 2-4 hours; after the crosslinking is completed, it is quenched with 0.1 mol / L glycine solution for 30 minutes.

8. A method for preparing a decellularized dermal biological patch for hernia repair according to claim 6, characterized in that: In step (2), the stirring process involves first dissolving carboxymethyl chitosan, sodium hyaluronate, chondroitin sulfate, and glycerin in deionized water, and stirring at 30-40℃ and 200-300rpm until completely dissolved to obtain a premixed solution; then adding the modified zinc tannate nanocomposite stock solution to the premixed solution, and continuing to stir for 20-40 minutes to ensure uniform dispersion, maintaining the pH at 6.8-7.4, and finally sterilizing through a 0.22μm filter membrane to obtain the coating solution.

9. A method for preparing a decellularized dermal biological patch for hernia repair according to claim 6, characterized in that: In step (3), the pre-freezing temperature is -18 to -25°C and the time is 1.4 to 3.2 hours, and the deep freezing temperature is -75 to -90°C and the time is 3 to 5 hours.

Citation Information

Patent Citations

  • Organ-like culture medium of HPV infected cervical tissue and culture method of organ-like culture medium

    CN116716234A

  • Tissue adhesive as well as preparation method and application thereof

    CN119701067A